2022
DOI: 10.1007/s10965-022-03011-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced structural, optical, electrical properties and antibacterial activity of PEO/CMC doped ZnO nanorods for energy storage and food packaging applications

Abstract: The zinc oxide nanorods (ZnONRs) have been successfully prepared via sol-gel way. A series of Poly(ethylene oxide) and Carboxymethyl cellulose (PEO/CMC) blend samples lled with different concentration of ZnONRs were prepared using casting method. Transmission electron microscopic (TEM) image showed that the synthesized ZnONPs had a diameter in the range of 29.29 to 59.09 nm. These samples were characterized by different analytical techniques. On the basis of results obtained from XRD and FT-IR analysis, blends… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…The 225 nm peak’s strength increases and is shifted to longer wavelengths when the concentration of TiO2 increases (redshift). As determined by XRD analysis, the shift of the TiO 2 NPs could be due to changes in crystallinity, which suggest complexation/homogeneity, and differences in the energy gaps between polymeric matrices and TiO 2 NPs [ 4 , 21 , 23 , 24 ]. The last two samples (at 0.4 and 0.8 wt.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 225 nm peak’s strength increases and is shifted to longer wavelengths when the concentration of TiO2 increases (redshift). As determined by XRD analysis, the shift of the TiO 2 NPs could be due to changes in crystallinity, which suggest complexation/homogeneity, and differences in the energy gaps between polymeric matrices and TiO 2 NPs [ 4 , 21 , 23 , 24 ]. The last two samples (at 0.4 and 0.8 wt.…”
Section: Resultsmentioning
confidence: 99%
“…As an effective coating technique, the PEO polymer has been used to produce antimicrobial coatings on the surfaces of bio-medical devices. Although PEO coating alone can enhance the antimicrobial activity of materials, additions of nanofiller with good antibacterial activity into the PEO matrix can further double the antimicrobial activity [ 4 , 5 ]. Since carboxymethyl cellulose (CMC) polymer is amorphous, it facilitates the movement of ions within the blend matrix by increasing the number of amorphous regions.…”
Section: Introductionmentioning
confidence: 99%
“…Tarabiah et al (2022) prepared a biodegradable blend of polyethylene oxide and carboxymethylcellulose (CMC) with loaded ZnO nanorods as a filler. The authors demonstrated that PEO/CMC/ZnO nanobiocomposites could be used as a UV mask and demonstrate antimicrobial activity against S. aureus and E. coli [ 465 ]. Su et al (2017) examined biocompatible polymers in detail, such as sodium alginate (SA) and carboxymethylcellulose (CMC) loaded with silver nanoparticles (AgNP).…”
Section: Application Of Biodegradable Polymers and Antibacterial Poly...mentioning
confidence: 99%
“…The XRD shows that the peak at 2θ ≈ 19.7° has further decreased and that the crystallinity of the nanoparticles grew at the expense of the CMC/ PVA/PEDOT:PSS mixture matrix. This enhancement in the blend's amorphous nature is indicative of high ionic diffusivity, which can result in enhanced ionic conductivity [4].…”
Section: Xrd and Tem Analysismentioning
confidence: 99%
“…Its structure is composed of hydroxyl (OH) and carboxylate (COO) groups that promote interactions between the various fillers in the polymeric system [3]. Among CMC's unique characteristics are its transparency, high viscosity, biocompatibility, and biodegradability [4]. It is used in a variety of applications, such as paper manufacturing, textile printing, and medication delivery [5].…”
Section: Introductionmentioning
confidence: 99%